Cell Cycle Regulation and Differentiation in Cardiovascular and Neural Systems - Giordano, Antonio; Galderisi, Umberto; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2010)
Complex physiopathological relationships have been proven to exist between two of the body’s most vital organs; the brain and the heart. In Cell Cycle Regulation and Differentiation in Cardiovascular and Neural Systems Antonio Giordano, Umberto Galderisi and a panel of the most respected authorities in their field offer an in-depth analysis of the differentiation process in two systems that have profound relationships with one another. The text looks at several aspects of the cardiovascular and nervous systems from a new point of view, describing the differences and similarities in their differentiation pathways with an emphasis on the role of cell cycle regulation and cell differentiation. Topics discussed include neurogenesis in the central nervous system, neural stem cells, and the basic-helix-loop-helix transcription factors in neural differentiation. Ground-breaking and authoritative, Cell Cycle Regulation and Differentiation in Cardiovascular and Neural Systems is a must have for all researchers in cardiovascular medicine and neuroscience and will prompt the scientific community to perceive cell cycle regulation and differentiation under a novel and more comprehensive light.
to Cell Cycle and Differentiation -- Short Introduction to the Cell Cycle -- The Basic Helix-Loop-Helix Transcription Factors in Neural Differentiation -- Transcription Factors and Muscle Differentiation -- Stem Cells -- The Neural Stem Cells -- Cardiac Stem and Progenitor Cells -- Muscle Stem Cells -- Marrow Stromal Mesenchymal Stem Cells -- Cell Cycle and Differentiation in the Nervous System -- Neurogenesis in the Central Nervous System: Cell Cycle Progression/Exit and Differentiation of Neuronal Progenitors -- Cell Cycle and Differentiation in the Cardiovascular System -- Cell Cycle and Differentiation in the Cardiovascular System -- Cell Cycle and Differentiation in Vessels -- Cell Cycle and Differentiation in the Muscle -- Cell Cycle Regulation in Myogenesis.
Keywords: Cardiology; Human anatomy; Neurology .; Neurosciences; Cardiology; Anatomy; Neurology; Neurosciences